Perspektif Perlindungan Pemegang Hak Desain Industri Giroskop Berdasarkan Undang-Undang Desain Industri - Vielly , Wong (Tribuere, 2022)
PT. ACME Indonesia objected to the Gyroscope Mixer Industrial Design held by Coloriance CO. LTD. PT's lawsuit. ACME Indonesia is seeking to cancel Industrial Design owned by Coloriance CO.LTD. which is listed on the Industrial Design General List. The question is how the legal protection for the holder of the Industrial Design Rights of Gyroscope Mixer (Mixers) in terms of having elements of novelty under Act No. 31 of 2000? And is the judgment of the Commercial Court Judge on Industrial Design between PT. ACME Indonesia with Coloriance CO.LTD. is in compliance with Act No. 31 in 2000?. Research is done with normative type, with a rule and case approach. The data used is secondary data, the primary legal material of the Industrial Design Act, its regulations and Decision No. 01/Pdt.Sus-Design Industrial/2020/PN. Jkt.Pst. Research properties are descriptive and analyzed qualitatively. The Chamber of Commercial Court Judges fully admitted the PT's complaint. ACME Indonesia for finding some facts that indicate that Coloriance's Mixer Gyroscope does not meet the element of novelty. The facts found are as follows, Coloriance had made disclosures long before the date of registration application, found several similar mixing machines both at home and abroad.